1975
DOI: 10.1083/jcb.67.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Gametic differentiation in Chlamydomonas reinhardtii. III. Cell wall lysis and microfilament-associated mating structure activation in wild-type and mutant strains.

Abstract: Cell fusion between mating type plus (mr +) and minus (rot-) gametes ofChlamydomonas reinhardtii is analyzed structurally and subjected to experimental manipulation. Cell wall lysis, a necessary prelude to fusion, is shown to require flagellar agglutination between competent gametes; glutaraldehyde-fixed gametes ("corpses") of one mating type will elicit both agglutination and cell wall lysis in the opposite mating type, whereas nonagglutinating impotent (imp) mutant strains are without effect. The fusion proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 22 publications
1
100
0
1
Order By: Relevance
“…In addition to the fertilization tubules and flagella it was possible to clearly visualize the eyespot and their lipid globules using FE-SEM, which have not been observed using conventional SEM (Goodenough and Weiss 1975, Forest 1983, 1987. Since the eyespots were clearly recognized, it becomes possible to directly determine the spatial relationship of flagella-eyespot-cell fusion site in the gamete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the fertilization tubules and flagella it was possible to clearly visualize the eyespot and their lipid globules using FE-SEM, which have not been observed using conventional SEM (Goodenough and Weiss 1975, Forest 1983, 1987. Since the eyespots were clearly recognized, it becomes possible to directly determine the spatial relationship of flagella-eyespot-cell fusion site in the gamete.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that the cell fusion sites of the gametes occupy different positions between the opposite mating types in several green algae (see Miyamura and Nagumo 2007). This was first indicated in biflagellate isogametes of chlorophycean alga Chlamydomonas reinhardtii Dangeard (Holmes andDutcher 1989, Gaffal et al 1991), in which cell fusion site is differentiated to specialized cell membrane "mating structure" (Goodenough and Weiss 1975). The mating structure of mt Ϫ gamete is located at the cell apex on the same side of the flagellar basal bodies as the eyespot (photoreceptive device), whereas the mt ϩ structure is located in the opposite position (Holmes andDutcher 1989, Gaffal et al 1991, see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Un tel processus a déjà été envisagé pour un certain nombre de Ptéridophytes (Tourte, 1971 ;Duckett et Bell, 1972). Le rôle des flagelles dans la reconnaissance a particulièrement été étudié chez diverses espèces de Chamydomonas (Cavalier-Smith, 1975 ;Triemer et Brown, 1975 ;Goodenough et Weiss, 1975 ;Weiss et coll., 1977 ;Wiese et Wiese, 1978 ;Mesland et Van den Ende, 1979 ;Snell et Roseman, 1979). Cependant, le premier point de fusion concerne des zones différenciées du plasmalemme chez Chlamydomonas et Ulva lactuca (Melkonian, 1980) et toute généralisation peut paraître encore préma-turée.…”
Section: Discussionunclassified
“…Various changes during the mating reaction are triggered by the adhesion between flagella of opposite mating types, which induces an increase in the intraflagellar cAMP concentration (6,18). When gametic cells were activated by addition of flagella isolated from gametes of opposite mating types, the level of actin mRNA increased in wild-type cells and the level of NAP mRNA increased in ida5 cells (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%